The anatomical knowledge of Joaquín Albarrán (1860-1912) - Poulakou-Rebelakou, Effie L.; Karamanou, Marianna I.; Mylonas, Anastasios I. (Italian Journal of Anatomy and Embryology, 2015)
Joaquín Maria Albarrán (1860-1912) is broadly known as a brilliant mind and a pioneer of modern urology, in spite of his short life. Born in Cuba and being early an orphan, he was sent to Barcelona to study Medicine. Graduate at the age of seventeen, he continued his studies in Paris, where he was trained in surgery and urology, and spent the rest of his life having an extraordinary career as urology surgeon, chief of the Urology Department in Necker Hospital and professor at Paris Faculty of Medicine. Since his first studies, he had been passionate with anatomy, histology, pathology and microbiology and embodied in his books, today considered as classics, a great amount of the special knowledge he had for these fields and the most accurate descriptions of the operative techniques for the urinary tract system.